2008
DOI: 10.1111/j.1750-3841.2008.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Gelling System of Low‐Methoxy Pectins Produced by Demethoxylating Reaction of Pectin Methyl Esterase

Abstract: After deesterification of commercial pectins with a pectin methyl esterase (PME), their gelling properties were characterized using instrumental texture analysis. The final degree of esterification (DE) of the high- and low-methoxy pectins reached approximately 6% after the PME treatment, while deesterification of low-methoxy amidated pectin stopped at 18% DE. Furthermore, DE of high-methoxy pectin was tailored to be 40%, which is equivalent to the DE of commercial low-methoxy pectin. As a result, significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 24 publications
3
14
0
3
Order By: Relevance
“…It would be why pectins obtained by physical/enzymatic treatments exhibited lower viscosity than chemically-extracted pectins at the same concentrations. These results were in good agreement with previous studies that reported a decrease in the hardness of pectins gels with increasing degree of esterification (Kim et al, 2008). In addition, since viscosity is a function of molecular weight, the viscosity variations between two pectin samples could be partly attributed to their molecular weights.…”
Section: Resultssupporting
confidence: 93%
“…It would be why pectins obtained by physical/enzymatic treatments exhibited lower viscosity than chemically-extracted pectins at the same concentrations. These results were in good agreement with previous studies that reported a decrease in the hardness of pectins gels with increasing degree of esterification (Kim et al, 2008). In addition, since viscosity is a function of molecular weight, the viscosity variations between two pectin samples could be partly attributed to their molecular weights.…”
Section: Resultssupporting
confidence: 93%
“…They showed greatly increased sensory firmness, springiness, coarseness of mass, and chewiness, but reduced sensory adhesiveness, cohesiveness, and mouthcoating. In our previous study, the textural properties of PME-treated pectin gels based on the results of instrumental texture profile analysis were reported (Kim et al, 2008). The sensory test results from this study verified previous texture profile analysis results.…”
Section: Effects Of Molecular Differences Of Pectin On the Textural Psupporting
confidence: 91%
“…The treated pectins were designed to have different molecular weights, degrees of esterification, and degrees of amidation (DA). Detailed descriptions of the PME-de-esterification and the molecular properties have been reported in our previous study (Kim, Yoo, Kim, Park, & Yoo, 2008). The molecular properties of the pectins are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analyses conducted in this study, the pectin extracted from apples would be within the range of HM pectins because, in most of the treatments, a degree of esterification higher than 50% was obtained, indicating that the pectin is suitable for use in the manufacture of jams, jellies and preserves due to its gelling property (Kim et al, 2008). A greater amount of pectin was obtained at a lower pH, but this treatment also produced a lower quality pectin due to its low degree of esterification.…”
Section: Degree Of Esterification (De)mentioning
confidence: 79%